Exploring the impact of prenatal perfluoroalkyl and polyfluoroalkyl substances exposure on blood pressure in early childhood: A longitudinal analysis - Bowen Du; Qianchuo Wang; Zhikang Xu; Hualin Wang; Zhuoyan Li; Yujian Wu; Yiwei Niu; Qianlong Zhang; Xi Zhang; Kun Sun; Jian Wang (Ecotoxicology and Environmental Safety, 2024)
Previous research investigating the correlation between prenatal exposure to per- and polyfluoroalkyl substances (PFAS) and subsequent blood pressure (BP) in offspring has yielded limited and contradictory findings. This study was conducted to investigate the potential relationship between maternal PFAS levels during pregnancy and subsequent BP in early childhood. A total of 129 expectant mothers from the Shanghai Birth Cohort were included in the study. Using high-performance liquid chromatography/tandem mass spectrometry, we measured ten PFAS compounds in maternal plasma throughout the pregnancy. When the children reached the age of 4, we examined their systolic BP (SBP) and diastolic BP (DBP), along with mean arterial pressure (MAP) and pulse pressure (PP). Data interpretation employed multiple linear and logistic regression models, complemented by Bayesian kernel machine regression (BKMR).We found that the majority of PFAS concentrations remained stable during pregnancy. The linear and BKMR models indicated a positive relationship between the PFAS mixture in maternal plasma and offspring's DBP and MAP, with perfluorohexanesulphonic acid (PFHxS) having the most significant influence (PFHxS and DBP [first trimester:β=3.03, 95%CI: (1.01,5.05); second trimester: β=2.35, 95%CI: (0.94,3.75); third trimester: β=2.57, 95%CI:(0.80,4.34)]; MAP [first trimester:β=2.55, 95%CI: (0.64,4.45); second trimester: β=2.28, 95%CI: (0.95,3.61); third trimester: β=2.35, 95%CI:(0.68,4.01)]). Logistic regression highlighted an increased risk of prehypertension and hypertension in offspring with higher maternal PFHxS concentrations during all three trimesters [first trimester: OR=2.53, 95%CI:(1.11,5.79), second trimester: OR=2.05, 95%CI:(1.11,3.78), third trimester: OR=3.08, 95%CI:(1.40,6.79)]. A positive correlation was identified between the half-lives of PFAS and the odds ratio (OR) of prehypertension and hypertension in childhood (β=0.139, P=0.010). In conclusion, this research found maternal plasma PFAS concentrations to be positively associated with BP in offspring, with PFHxS showing the most significant influence. This correlation remained consistent throughout pregnancy, and this effect was proportional to the half-lives of PFAS.